2003
DOI: 10.1128/iai.71.1.155-162.2003
|View full text |Cite
|
Sign up to set email alerts
|

Lipooligosaccharide-DeficientNeisseria meningitidisShows Altered Pilus-Associated Characteristics

Abstract: Molecular interaction between host mucosal surfaces and outer membrane components of microbes is crucial in the infection process. The outer membrane of pathogenic Neisseria contains surface molecules such as pili, PilC, and Opa and a monolayer of lipooligosaccharide (LOS), all of which are involved in the interaction with host cells. Pili mediate the initial attachment to human epithelial cells, which is followed by tight contact between bacteria and the eucaryotic cells, leading to bacterial invasion. To fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 55 publications
6
43
0
Order By: Relevance
“…Bacterial adherence to the surface of epithelial cells plays a critical role in colonization and is believed to be the first step in the pathogenesis of microbial infections. It has been reported that several LOSs from respiratory tract bacteria are associated with bacterial adherence (2,18,20,41,44). Fitzgerald et al showed that the bacterial adherence of M. catarrhalis might be mediated by carbohydrate moieties (12).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial adherence to the surface of epithelial cells plays a critical role in colonization and is believed to be the first step in the pathogenesis of microbial infections. It has been reported that several LOSs from respiratory tract bacteria are associated with bacterial adherence (2,18,20,41,44). Fitzgerald et al showed that the bacterial adherence of M. catarrhalis might be mediated by carbohydrate moieties (12).…”
Section: Discussionmentioning
confidence: 99%
“…LPS is an essential OM component in E. coli, but not in Neisseria meningitidis, which can exist without LPS as demonstrated by the viability of lpxA mutants, in which the gene involved in the first step in LPS biosynthesis is disrupted (9,10). These lpxA mutants are completely devoid of LPS.…”
mentioning
confidence: 99%
“…Apparently, the lpt mutations render the cells less competent. This is likely related to their low LPS content, because a meningococcal lpxA mutant, which does not produce any LPS, was also reported to be severely impaired in competence (29). Therefore, we created conditional strains by first introducing a plasmid containing the relevant gene under IPTG control in strain HB-1, followed by inactivation of the chromosomal gene copy in the presence of IPTG.…”
Section: Putative Lps Transport-associated Loci In N Meningitides-mentioning
confidence: 99%